ASHRAE GreenGuide - Design Construction and Operation of Sustainable Buildings (5th Edition).
"Provides information on green-building design. Concerned with sustainable, high-performance projects"-- Provided by publisher.
Keywords: Sustainable buildings -- Design and construction.; Sustainable buildings -- United States -- Design and construction.; Sustainable architecture.; Buildings -- Environmental engineering.; Sustainable construction.; elektronické knihy; electronic books